Número de células e sinalização intracelular no córtex e formação hipocampal de ratos fisicamente ativos no período pós-natal do desenvolvimento cerebral - Victorino, Angélica Begatti [UNIFESP] (2016)
Objective:Better cognitive performance and greater cortical and hippocampal volume have been observed in individuals who underwent aerobic exercises during childhood and adolescence. A possible explanation for these beneficial effects is that juvenile physical exercise enables better neural development hence more cells and neuronal circuities. It is probable that such effects occurthrough intracellular signaling proteins associated to cell growth, proliferation and survival. Based on theseinformation, we evaluated the number of neuronal and non-neuronal cells and the expression and activation of intracellular proteins(ERK, CREB Akt, mTOR and p70S6K) in the cerebral cortex and hippocampal formation of rats submitted to an aerobic exercise program during adolescent period.Methods: Male Wistar rats aged 21 postnatal days old (P21) were divided into two groups: exercise (n=12) and control (n=12). Animals in the exercise group were submitted to daily exercise on the treadmill between P21 and P60. After the aerobic exercise program (P60), it was investigated the number of neuronal and non-neuronal cells and the expression and activation of Akt, mTOR, p70S6K, ERK and CREB (total and phosphorylated) in the cortex and hippocampal formation of rats from the exercise and control groups. To quantify the number of cells, we used the isotropic fractionation method. To investigate the intracellular signaling pathways, we used MAGPIX® technology. Results:Results showed that physical exercise increases the number of cortical neuronal and non-neuronal cells and of hippocampal neuronal cells in adolescent rats. Moreover, it was found a mTOR overexpression in cortical region of adolescent rats exercised. Conclusion:These findings indicate a significant cellular proliferative effect of aerobic exercise on the cerebral cortex in postnatal development.